2014
DOI: 10.1097/inf.0000000000000269
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Childhood Pneumonia and Infant Mortality Rates Following Introduction of the 13-valent Pneumococcal Conjugate Vaccine in Nicaragua

Abstract: Within the first 2 years of a PCV-13 immunization program in Nicaragua, we observed lower rates of hospitalizations and ambulatory visits for pneumonia among children of all ages and a lower infant mortality rate. Lower rates of pneumonia among age groups not eligible to receive PCV-13 suggest an indirect effect of the vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 16 publications
3
64
2
Order By: Relevance
“…Within the first two years of a PCV13 immunization program in Nicaragua, provided as the only PCV, investigators observed statistically significant lower risks of pneumonia hospitalizations, compared to the pre-vaccination period: 33% reduction in infants <1 year-old (0.67; 0.59–0.75) and 26% in children 1-<2 years-old (0.74; 0.67–0.81) [19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Within the first two years of a PCV13 immunization program in Nicaragua, provided as the only PCV, investigators observed statistically significant lower risks of pneumonia hospitalizations, compared to the pre-vaccination period: 33% reduction in infants <1 year-old (0.67; 0.59–0.75) and 26% in children 1-<2 years-old (0.74; 0.67–0.81) [19].…”
Section: Discussionmentioning
confidence: 98%
“…Investigators in Nicaragua (3+0 schedule) recently observed lower rates of all-cause pneumonia hospitalizations among children after the introduction of PCV13 immunization through the GAVI Alliance [19]. Furthermore, two recent studies from Uruguay and France (both 2+1 schedules) reported a significant reduction among children <2 years old of consolidated pneumonia and community-acquired pneumonia when transitioning from PCV7 to PCV13 [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…Uruguay and Nicaragua) [Becker-Dreps et al 2014;Pirez et al 2014]. This is the first Mexican study based on active surveillance that shows early findings of the effectiveness of PCV-13 on reduction of overall IPD, decrease in pneumococcal serotype 19-A, and early effects of pneumococcal meningitis and fatalities in children.…”
Section: Resultsmentioning
confidence: 99%
“…USA, Nicaragua, Spain, Denmark, France, Ontario, Israel, South Africa, and UK when high vaccine coverage was achieved. [49][50][51][52][53][54][55][56] However, in settings with vastly different environmental risk factors, mixing patterns, family structures, and culture such as Malaysia and Hong Kong, it is uncertain the extent to which similar effects will be observed. In the absence of country-specific estimates of herd effects, it was assumed that herd effects observed in these 2 countries would be very similar to that observed in the US post-PCV7 era.…”
mentioning
confidence: 99%